2018
DOI: 10.1177/1071100718768225
|View full text |Cite
|
Sign up to set email alerts
|

Lateralizing Calcaneal Osteotomies and Their Effect on Calcaneal Alignment: A Three-Dimensional Digital Model Analysis

Abstract: For the surgical treatment of cavovarus foot deformities, osteotomies with wedge resection in addition to lateralization enable more powerful correction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Finally, many calcaneal osteotomies require concomitant procedures [ 13 , 14 ], as can be seen in our series, where 91% of patients underwent some ancillary procedure (Broström, ankle arthroscopy, gastrocnemius lengthening, etc.) in the same surgical episode.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Finally, many calcaneal osteotomies require concomitant procedures [ 13 , 14 ], as can be seen in our series, where 91% of patients underwent some ancillary procedure (Broström, ankle arthroscopy, gastrocnemius lengthening, etc.) in the same surgical episode.…”
Section: Discussionmentioning
confidence: 76%
“…The general principle guiding this technique is that the more anterior the osteotomy is performed, the more the calcaneal tuberosity can be mobilized. However, the sural nerve, the medial plantar branch, and the lateral plantar branch are at high risk if the osteotomy is performed more anteriorly [ 3 , 7 , 14 , 15 ]. Kraus et al reported that lateral translation provides greater correction of varus deformity, although it may cause significant additional shortening of the calcaneus [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 Lateralization of the calcaneus also transforms the gastrocnemius and soleus muscles from a deforming varus force to a correcting valgus force on the hindfoot. 5 We had unanimity that an osteotomy is often, but not always, needed in CMT foot reconstruction. There are numerous techniques for a calcaneal osteotomy.…”
Section: Calcaneal Osteotomymentioning
confidence: 99%
“…On the other hand, few reports have discussed the possibility of peri-operative neurovascular compromise, despite this being a known complication [4]. Nerve injuries can occur during the approach [6,7], as a result of the osteotomy itself [4,6] or due to acquired iatrogenic tarsal tunnel syndrome [4,8], amongst others. Lateral structures, such as the sural nerve and lateral calcaneal nerve, are at risk during exposure in the lateral approach to the calcaneus [7,9], while the posterior tibial nerve and its calcaneal, medial plantar, and lateral plantar branches are at risk during osteotomy and medial or lateral displacement [9].…”
Section: Introductionmentioning
confidence: 99%